MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR IPA SISWA TUNANETRA DI SMPLB - NUR SAPUTRI, FINISYA (Jurnal Pendidikan Khusus, 2016)
Abstract The ability of blind children in understanding science concept was low so that it required orientation and mobility to help the readiness in learning using cooperative learning model of Think Pair Share (TPS) type. The purposes of this research were 1) to analyze whether there was implementation influence of cooperative learning model of Think Pair Share (TPS) type toward science learning result to the blind students in SMPLB-A YPAB Surabaya, 2) to analyze the learning activity of the blind students in SMPLB-A YPAB Surabaya toward the implementation of cooperative learning of Think Pair Share (TPS) type. The approach used was quantitative with pre-experiment kind and the design was one group pretest-posttest design. The data was collected by test method, observation, and documentation. The technique of data analysis used was statistic non parametric with n = 9 and α = 5% (1,96) and it was processed using Wilcoxon Match Pairs Test formula. The research result indicated that the average value of pretest was 40 and the average value of posttest was 70. The result of data analysis Z counted = 2,66 > Z table = 1,96. Ha was accepted it meant that there was implementation influence of cooperative learning model of Think Pair Share (TPS) type toward learning science result to the blind students in SMPLB-A YPAB Surabaya whereas the learning activity which was analyzed by giving treatment for 6 times meeting indicated good result with 71,4% value.   Keywords: Think Pair Share (TPS), learning science